Physical Model Experiment on Offshore Breakwater Project in Dongao Bay - CHEN Kai; HE Yong; WANG Shijun (Renmin Zhujiang)
Dongao Bay Breakwater Project is an important infrastructure for Zhuhaiisland development, which is of great significance to the development of inhabitedislands in Zhuhai. Based on the statistics of prototype observation data andnumerical simulation technology, this paper studies the wave characteristics andthe response of Dongao Bay to breakwater project by integral physical modelexperiment method, which provides scientific basis for comparison and optimizationof design schemes of Dongao Bay breakwater. The results show that, under naturalconditions, the wave energy convergence area is formed by E-pointing wave in thenorth of the bay mouth, and the effective wave height in the north is higher thanthat in the south. After the implementation of the project, the wave field inDongao Bay can be roughly differentiated into four typical areas: the coastal wavereflection enhancement area in the north bay, the refraction diffraction area inthe south bay, the overlay influence area of wave diffraction refraction in thebay, and the refraction reflection oscillation area in the bay. In terms ofoptimizing wave conditions, the difference between the schemes is not significant,but the breakwater head of single channel (scheme II) is affected by wave-inducedcurrent diffraction and oblique wave impact, resulting in structural instability.In general, when the shielding effect is similar, the scheme of double channelbreakwater (scheme I) is superior to the single channel scheme in terms ofstructural safety, intensive use of channel resources and shoreline resources.